Development of a patient satisfaction questionnaire (PSQ) for diabetes management in Thailand and Lao PDR. - Phayom Sookaneknun Olson; Chanuttha Ploylearmsang; Phoutsathaphone Sibounheuang; Santiparp Sookaneknun; Chanthanom Manithip; Suntaree Watcharadamrongkun; Paul W Jungnickel; Pattarin Kittiboonyakun (PLoS ONE, 2024)
In a cross-sectional analytical study, a Patient Satisfaction Questionnaire (PSQ) for diabetes management was developed and tested in Thailand and Lao PDR. A systematic review of qualitative studies was conducted to formulate themes of the PSQ. The 20-item PSQ was prepared in Thai and translated to Lao, with subsequent backward translation. Both versions were tested for reliability and construct validity using confirmatory factor analysis and structural equation modeling. The study was performed at a university hospital in Thailand and two central hospitals in Vientiane, Lao PDR. There were 300 diabetic patients from Thailand (n = 150) and Lao PDR (n = 150). The 5-factor Thai version showed 74.52% of total explained variance with good internal consistency and satisfactory goodness-of-fit indices (χ2/df = 1.91, GFI = 0.83, CFI = 0.98, SRMR = 0.063, RMSEA = 0.078). The five factors were 1) Standard of Service, 2) Diabetic Service, 3) Competency of Providers, 4) Competency of Pharmacists, and 5) Communication with Providers. For the Lao version, 20 items showed a 3-factor structure with a total explained variance of 71.09%. Goodness-of-fit indices for the Lao model were satisfactory (χ2/df = 2.45, GFI = 0.78, CFI = 0.95, SRMR = 0.075 and RMSEA = 0.095). The results showed the PSQ Thai and Lao versions were valid and reliable for assessing patient satisfaction with diabetes management, however more testing of the questionnaire is appropriate.